A formação docente e as crenças de professores em relação à matemática: uma ruptura possível? - Zat, Ancilla Dall'Onder (Universidade do Vale do Rio dos Sinos, 2012)
A long process is required to be a teacher. On the first education acquired each student brings knowledge and skills and beliefs, a lot of times so ingrained that the gradation on the bachelors degree can not change them. This case study investigates the relation between the teacher's graduation and the construct of beliefs that are evidenced on the practice in the classrooms by the Mathematics teachers. The question is: How are the Math teacher's beliefs built during the graduation and docent trajectory about its knowledge? How the teachers Mathematics beliefs lead its pedagogic practice with the fifth grade students of the Elementary School? The qualitative approach research uses the written narrative and recorded and transcribed interviews with six Mathematics teachers. The speech analysis of these teachers is theoretically based in Tardif, Nóvoa, Ponte, Ernest, Gómez Chacón, Vila e Callejo, Marcelo Garcia, Cunha e Perrenoud, etc. The speech analysis is structured in six main ideas: the option for the docent graduation; obtained knowledge and determinant subjects on the academic graduation; docent knowledge occurred from the stage and its consequences during the docent practice; the knowledge and it understanding by the teachers; apprenticeship - difficulties and possibilities; the Mathematics according to the teachers beliefs. The interviewed teachers' report clearly proves the academic graduation importance on the beliefs and conceptions' construct, as well its practice influence with the students. Although the personal points brought and the history of life of each one is powerful, the academic formation increased conceptions and contributed with a few changes. The force of the knowledge field was reinforced, but new possibilities and questioning were opened that did and still do the teachers keep looking for more spaces of formation.
Keywords: Crenças; Concepções; Formação inicial e continuada de professores de matemática; Saberes e práticas docentes; Belief; Conceptions; Initial and continued formation of Mathematics teachers; Docent practice and knowledge; ACCNPQ::Ciências Humanas::Educação